Designing Tourist Itineraries with Design Thinking and System Usability Scale: A Case Study of Uluwatu Island, Bali - Hanif Habibie; Shilva Humairah; Ella Riskhina Putri; Atikah Nurhayati; Dewi Ratnasari (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2024)
Purpose: This research aims to design a travel itinerary media that integrates necessary elements from various sources and presents them in an attractive and informative format. The approach used is Design Thinking, which places the user at the center of the design process. Method: The research employs the Design Thinking approach, which involves five main stages: Empathy, Define, Ideate, Prototype, and Test. Data were collected through direct observation, questionnaires, and analysis of tourist behavior and preferences. The resulting prototype was tested by a representative group of users to assess the functionality and usability of the travel itinerary design. Result: The study culminated in the creation of a tourist itinerary media design, developed through the Design Thinking process. This design effectively integrates essential elements from diverse sources, ensuring it is both visually appealing and informative. Crucially, user testing with the System Usability Scale (SUS) produced an average score of 76.75. This score reflects a high level of user satisfaction and confirms the system's strong usability, highlighting the design's potential for enhancing the tourist experience. The positive reception underscores the study's impact in offering a user-friendly and engaging tool for tourism planning. Contribution: The main contribution of this study is the development of a more innovative tourist itinerary design that is in line with user needs. Through the Design Thinking approach, this research provides practical guidance for designing relevant and effective solutions in the tourism industry context.